IMPLEMENTASI SISTEM AMONG UNTUK MENUMBUHKAN RASA CINTA TANAH AIR PADA PEMBELAJARAN TEMATIK MUATAN PPKN KELAS 3 SD N KARANGREJO KEBUMEN - Zahrotun Najah; Wachid Pratomo; Nadziroh Nadziroh; Chairiyah Chairiyah (Universitas Sarjanawiyata Tamansiswa, 2022)
The Among system encourages every child to become a member of society who is honest, independent, and responsible for the welfare of the homeland and humans in general. The purpose of this study is to describe the implementation of the Among system to foster a sense of love for the homeland in the thematic learning of the content of Civics for grade 3, describe the supporting factors experienced by teachers, describe the obstacles experienced by teachers, and solutions to overcome obstacles. This research method is qualitative research. Principal sources of information are principals, teachers, and students. Data collection techniques are observation, interviews, and documentation. This study uses triangulation techniques a test the validity of data and the credibility of the data. The data analysis technique used is the Miles and Huberman analysis technique consisting of data reduction, presentation, conclusion, and verification. The results of this study indicate that the Among method has been applied by the teacher but in writing it does not include a special method such as the Among method. The supporting factors experienced by teachers are adequate facilities and infrastructure, and the teacher's enthusiasm for learning gives a positive aura to students. Obstacles for teachers have practically been carried out in education and learning so that the application of the method does not experience too many obstacles. However, it cannot be implemented optimally. The teacher's solution is habituation, explaining the material by showing a video about how beautiful Indonesia is, explaining the profile of Pancasila teachers, and introducing the heroes through pictures.